2021
DOI: 10.3390/jcm10225275
|View full text |Cite
|
Sign up to set email alerts
|

Non-Surgical Periodontal Therapy Could Improve the Periodontal Inflammatory Status in Patients with Periodontitis and Chronic Hepatitis C

Abstract: Non-surgical periodontal therapy (NSPT) is the first essential step for the management of any periodontitis patient. This study aims to evaluate the impact of NSPT on pro-inflammatory mediators’ regulation and on clinical parameters in periodontitis patients who suffer from chronic hepatitis C. At baseline, selected patients were clinically evaluated for their periodontal status. A subsequent quantitative assessment of C-reactive protein and pentraxin-3 in samples of gingival fluid was performed by Enzyme-Link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…PTX, also known as acute-phase proteins (APP), play a key role in the initiation of inflammation, primarily by protecting against pathogenic bacteria via complement activation. This role is supported by the fact that in GCF samples originating from patients diagnosed with periodontitis, PTX3 levels were significantly elevated, as compared to control groups [36,75]. These elevated GCF PTX3 levels also correlated with clinical periodontal parameters, suggesting an early up-regulated synthesis of this mediator by neutrophil cells, in response to periodontal bacterial aggression [36].…”
Section: Periodontitis and Chronic Hepatitis Cmentioning
confidence: 91%
See 1 more Smart Citation
“…PTX, also known as acute-phase proteins (APP), play a key role in the initiation of inflammation, primarily by protecting against pathogenic bacteria via complement activation. This role is supported by the fact that in GCF samples originating from patients diagnosed with periodontitis, PTX3 levels were significantly elevated, as compared to control groups [36,75]. These elevated GCF PTX3 levels also correlated with clinical periodontal parameters, suggesting an early up-regulated synthesis of this mediator by neutrophil cells, in response to periodontal bacterial aggression [36].…”
Section: Periodontitis and Chronic Hepatitis Cmentioning
confidence: 91%
“…Serum amyloid P and CRP are two minor members of this family. One of the long proteins in this family, plasma pentraxin 3 (PTX3), is detected in significantly higher concentrations in patients with steatohepatitis than in those without [36]. Patients with more severe forms of NAFLD have higher serum concentrations of this protein, and higher levels of this protein are associated with more severe forms of hepatic fibrosis.…”
Section: Periodontitis and Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…This mechanism is also found in degenerative hepatic conditions (as CHC and MAFLD). The inflammatory reaction in both periodontitis and hepatic conditions is driven by the same pro-inflammatory mediators, thus generating the hypothesis that the two type of conditions may share a pathogenic connection [ 54 , 55 ].…”
Section: Periodontitis and Liver Diseasesmentioning
confidence: 99%
“…The evaluation of the periodontal and dental status of periodontitis patients with CHC has shown that it was significantly more negatively modified than that of non-CHC periodontitis participants, in terms of tooth loss, number of periodontal pockets, periodontal pocket depth, clinical attachment loss and gingival index [ 55 ]. Furthermore, periodontitis + CHC patients exhibited significantly elevated gingival fluid levels of specifically-hepatic-synthetized enzymes, such as aspartate-aminotransferase and alanine-aminotransferase [ 56 , 57 ].…”
Section: Periodontitis and Liver Diseasesmentioning
confidence: 99%
“…Pharmacological intervention and surgery are considered the gold standard therapeutic protocol for advanced periodontitis, which may be associated with a high level of displeasure in the patient 3 . Although non-surgical treatment can improve important clinical parameters, microbial pathogens are not significantly reduced and this approach is not also effective in moderate to severe periodontal lesions 4 6 . Periodontitis is a polymicrobial disease and Porphyromonas gingivalis , as one of the most common bacterial causes, forms a microbial biofilm in the periodontium and on the teeth through the expression of various virulence factors, which eventually leads to treatment failure 7 .…”
Section: Introductionmentioning
confidence: 99%